Peningkatan Kemampuan Pemecahan Masalahan Melalui Penerapan Model Pembelajaran Problem Based Learnig (PBL) - Syibran Mulasi (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2017)
The discussion is focused in the application of learning the problem based learning (PBL)on the increase in students ability to solve the problem. In his discussion use a qualitativeapproach with the data presented shaped descriptive, by digging on books that have themost relevance to topic, shelled and analyzed rigorous adherence to the purpose of thediscussion. Of reference by which used referral from a variety of sources and journalthat support problems. Such as books kind of classroom, educational psychology andother reference having the relationship with matter. Said the outcome of his discussions,learning the problem based learning (PBL) effort to improve the ability of students tryingto settle the case teachers give. Students more accustomed to the problem and get itdone by method and way of thinking that more openly critical and to make it rational. Inaddition to the, liveliness the teaching and learning process more robust because studentsare required to capable of beker.